Erratic behavior of nitric oxide within the immune system: illustrative review of conflicting data and their immunopharmacological aspects - Zidek, Z; Masek, K (International journal of immunopharmacology, 1998)
The literature data assembled in this article document the variation of immunobiological effects of nitric oxide (NO). A number of factors are obviously responsible for the diversity, ranging from inactivity, alleviation, but not rarely to exacerbation of certain pathogenetic processes. A better understanding of NO interactions with the immune system can only be reached if more complex experimental designs to study the effects of reactive nitrogen species are adopted in the future. They should integrate major participating variables and take into account pharmacodynamic/kinetic aspects of NO production in triggering the ultimate effects. If manipulation of NO in the organism by means of recently developed NO inhibitors and NO donors is to become a rational tool of immunopharmacological strategies, detailed knowledge of their pharmacologies and toxicologies is urgently needed in order to differentiate between the effects of NO and other side effects. Hopefully, this approach could improve the predictability of the clinical outcomes of NO manipulation.
Keywords: donory oxidu dusnatého; Cytotoxicity, Immunologic; Endotoxemia; Encephalomyelitis, Autoimmune, Experimental; autoimunitní nemoci; Humans; druhová specificita; imunitní systém; cytokiny; oxid dusnatý; synthasa oxidu dusnatého; krysa rodu Rattus; Immune System; Inflammatory Bowel Diseases; lidé; zvířata; Nitric Oxide; myši; Nitric Oxide Synthase; infekce; encefalomyelitida autoimunitní experimentální; apoptóza; Arginine; Autoimmune Diseases; Mice; endotoxemie; idiopatické střevní záněty; Isoenzymes; izoenzymy; cytotoxicita imunologická; Neoplasms; Cytokines; arginin; Species Specificity; nádory; Rats; Animals; Histocompatibility Antigens Class II; Nitric Oxide Donors; MHC antigeny II. třídy; Apoptosis; Infections